Working from home during pandemic Covid-19: Effects of mobile technology use, supervisor support and job insecurity on employee’s role stress and job satisfaction - Edward Rorong (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
This study is to examine the relationship among mobile technology use, supervisor support, job insecurity, role stress and job satisfaction during working from home (WFH) in pandemic Covid-19. A descriptive research using questionnaires were distributed to employees in Jakarta areas (Jabodetabek). A total of two hundreds forty four valid questionnaires were collected. Factor analysis and regression analysis were used in this study. Based on the result of analysis, note that mobile technology use, supervisor support and job insecurity each have significant effect on role stress. In testing direct effect on job satisfaction, supervisor support, job insecurity and role stress were statistically significant, while mobile technology not significant. Role stress were mediating supervisor support and job insecurity toward job satisfaction. The findings of this study provide insight for company’s policies and strategies in adopting WFH/telecommuting activity as well as providing necessary support for employees knowing that WFH/telecommuting is not a work culture In Indonesia. Few research has been studied the impact of mobile technology use, supervisor support and perception of job insecurity towards to role stress and job satisfaction in the pandemic Covid-19 context.